ADAPTIVE IDENTIFICATION ALGORITHM DYNAMIC CONTROL OBJECTS - Antonov , V. K. (Problems of Informatization and Management, 2005)
An adaptive algorithm for the identification of dynamic control objects is proposed, based on the second Lyapunov method, characterized in that, in order to regularize the identification process, the behavior of the auxiliary function is subject to an auxiliary differential equation.